Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in diagnosis of mediastinal lesions - Ricardo Sales dos Santos; Marcia Jacomelli; Juliana Pereira Franceschini; Iunis Suzuki; Altair da Silva Costa Jr.; Christina Shiang; Addy Lidvina Mejia Palomino (Einstein (São Paulo))
ABSTRACT Objective To describe the results of endobronchial ultrasound-guided transbronchial needle aspiration in making diagnosis of mediastinal injuries associated to different causes. Methods A retrospective cross-sectional study of patients submitted to Endobronchial ultrasound-guided transbronchial needle aspiration at a private organization, between June 2013 and October 2016. All cases referred for collection of lymph nodes or peritracheal/peribronchial masses by endobronchial ultrasound-guided transbronchial needle aspiration, and evaluated through tomography or PET-CT were included. Interventional pulmonologists and thoracic surgeons with experience in the method did the procedures. Rapid on-site evaluation of fine needle aspiration was performed by an experienced pathologist. Material analysis included cytological smear and cytopathological analysis of paraffin-embedded cell blocks. Other specific analyses (immunocytochemistry, tests and cultures of infectious agents) were performed whenever necessary. Results We included 72 patients; 6 were excluded for presenting endobronchial lesions in which bronchoscopic biopsy could be performed, or intrathoracic lesions that were not accessible by endobronchial ultrasound-guided transbronchial needle aspiration. The mean age of 66 patients included for analysis was 61.17 years (±14.67 years), with a predominance of males (64%). Endobronchial ultrasound-guided transbronchial needle aspiration was definitive for diagnosis in 60 cases (91%). Three cases (4.5%) had inconclusive test results. There were no major complications related to the procedure. Conclusion Endobronchial ultrasound-guided transbronchial needle aspiration had a high diagnosis yield, with minimal morbidity, being an excellent option for diagnostic approach of patients with lymphadenopathy or intrathoracic lesions, and for neoplasm staging.